Mapping a Danger Zone of the Dorsal Nerve of the Clitoris: Implications in Female Cosmetic Genital Surgery. (29th November 2021) - Gordon, Victoria; Rowe, Joanna; Grubb, Lauren; Lewis, Adam; Johnson, Kenneth; Segars, Larry; Surek, Christopher; McCumber, Travis; Willet, Gilbert M.; Olinger, Anthony
Abstract : Background: The literature regarding the route of the dorsal nerve of the clitoris is sparse and lacks surgical focus. With an increasing number of procedures being performed on the labia, it is important to elucidate the route and note any variation from normal of the nerve. Methods: Fifty-one cadavers were dissected to yield 97 dorsal nerve of the clitoris samples. Measurements were taken from (1) the dorsal nerve of the clitoris penetration point of the perineal membrane to the urethra, (2) the nerve's penetration point of the perineal membrane to the pubic bone, (3) the angle of the clitoris to the branch point of the dorsal nerve of the clitoris, and (4) the branch point of the nerve to the distalmost point of the glans clitoris. Any anomalous branching patterns of the dorsal nerve of the clitoris were recorded and classified. Results: The means and standard deviations of each measurement were used to create a surgical danger zone. The mean of each measurement was (1) 34.63 mm, (2) 5.74 mm, (3) −3.07 mm, and (4) 30.40 mm, respectively. In addition, six distinct branching patterns were observed, organized, and classified based on the location and number of branches observed. Conclusions: The dorsal nerve of the clitoris has multiple branching patterns and typically travels along the same course in most women. Further investigation of the course and three-dimensional position of the dorsal nerve of the clitoris is warranted to preserve sexual sensation as the frequency of procedures involving the female pudendum increases.